2016
DOI: 10.1515/acve-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Apoptosis and Autophagy in Bovine Abortions Associated with Brucella Spp

Abstract: This study is aimed to evaluate the relationship between the severity of apoptotic and autophagic cell death based on the distribution of Brucella spp. antigens in the lung, liver, kidney, spleen, brain, heart, skeletal muscle, mesenteric lymph node, and thymus tissue from bovine fetuses aborted due to natural infection with Brucella spp. The distribution of Brucella spp. antigens was immunohistochemically examined in the tissues of 16 aborted fetuses from cattle diagnosed with Brucella spp. infection by a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Interestingly, B. neotomae ⌬virB4 infection showed both quantitative and qualitative attenuation, the latter, as observed during BLI studies, suggesting that T4SS contributes to colonization of the reticuloendothelial system (lymph nodes, spleen, and liver). We did not sample lymph nodes for CFU analysis; however, the absence of ⌬virB4 CFU isolated from the thymus, a site of long-term Brucella colonization in animals where examined (34,41,42), at any time point also supports a dissemination defect. This qualitative phenotype is reminiscent of the previously observed VirB-dependent colonization of mesenteric lymph nodes, spleen, and liver after gastrointestinal infection of BALB/c mice with B. melitensis 16 M (39) and the VirB-dependent reticuloendothelial system colonization of C57BL/6 mice by B. melitensis after intraperitoneal infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, B. neotomae ⌬virB4 infection showed both quantitative and qualitative attenuation, the latter, as observed during BLI studies, suggesting that T4SS contributes to colonization of the reticuloendothelial system (lymph nodes, spleen, and liver). We did not sample lymph nodes for CFU analysis; however, the absence of ⌬virB4 CFU isolated from the thymus, a site of long-term Brucella colonization in animals where examined (34,41,42), at any time point also supports a dissemination defect. This qualitative phenotype is reminiscent of the previously observed VirB-dependent colonization of mesenteric lymph nodes, spleen, and liver after gastrointestinal infection of BALB/c mice with B. melitensis 16 M (39) and the VirB-dependent reticuloendothelial system colonization of C57BL/6 mice by B. melitensis after intraperitoneal infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…Also, due to frequently occurring cross-reactions, serologic tests may yield false-negative results. Consequently, in cases of infected abortus, the determination of Brucella and Coxiella antigens with the highly sensitive and specifi c immunohistochemical methods is preferred [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The ATPbinding cassette (ABC) transporters use a variety of substrates such as amino acids, sugars, inorganic ions, polysaccharides, peptides and proteins [34] and several ABC transporters have been associated to the full virulence and survival of Brucella in vitro and in vivo, hence the increase in the transcription of genes that encode for these proteins could help in the virulence and survival of Brucella. MFS transporter was also observed to increase which functions as a secondary carrier that transports small solutes in response to chemiosmotic ion gradients and its upregulation may be important for the adaptation of Brucella in the ionic intracellular environment [12]. Furthermore, several transcripts for hypothetical protein were observed to increase suggesting their important roles in the survival of B. abortus in epithelial host cells, thus impose special attention to be studied further.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study investigated the relationship between the severity of apoptotic and autophagic cell death based on the distribution of Brucella antigens in the different tissues of aborted bovine fetuses due to natural infection and showed that the bacterial antigens were highly evident in the kidneys [11]. Interestingly, involvement of the renal parenchyma in the acute phase of brucellosis is very rare but generally manifested as acute interstitial nephritis, chronic interstitial nephritis or glomerulonephritis [12]. Although the involvement of kidney is not common, it has been reported that brucellosis is about ten times more prevalent in patients with renal failure and concluded that the disease can cause nephropathy [13].…”
Section: Introductionmentioning
confidence: 99%